Comparison of Economic Performance of Three Trade Free Zones in Iran (Kish, Gheshm, Chabahar) - Asgharizadeh, Ezzatollah; Ajalli, Mehdi; Momeni, Mansoor (European Journal of Economics and Business Studies, 2015)
Free zones (Export Processing Regions) with their special Functions including assisting export development and making new job opportunities can be of major help to economy of countries. Present paper aims at comparing economic performance of three free trade zones of Iran, Kish, Gheshm and Chabahar during first ten years of their activities (1973 to 2004) using four techniques of operational research, SAW (Simple Additive Weighting), TOPSIS (Technique for Order-Preference by Similarity to Ideal Solution), ELECTEER (Elimination et Choice Translating Reading) and Taxonomy and taking economic goals of these zones as indices. To this end, economic goals of these zones, that is attracting foreign and internal investment, making new job opportunities, enhancing value of export from these zones and their ability to attract internal and foreign tourists were considered as research indices. Results obtained showed that free zone of Gheshm had a better performance compared to two other zones and this is due to significant difference of its export value compared to other zones, with regard to the available statistics and the said indices. Kish and Chabahar respectively followed it.
Keywords: Performance assessment, free trade zone, Kish, Gheshm, Chabahar, SAW, ELECTRE? TOPSIS, TAXONOMY